Corrosion Rate Analysis of SS400 Steel Plates with Coating Variations in Artificial Seawater - Fairuza, Faaza Ihda; Syukron, Muhammad; Setyani, Atik; Fatmawati, Yulia (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
Low-carbon steel such as SS400 is highly susceptible to corrosion, particularly when exposed to marine environments or artificial seawater. One of the most common methods to mitigate corrosion is by applying protective coatings. This study aims to analyze the effect of coating type and thickness on the corrosion rate of SS400 steel using Electrochemical Impedance Spectroscopy (EIS). The samples were prepared by applying two types of coatings, epoxy and flintkote, with variations of one or two layers. The EIS results revealed that uncoated SS400 exhibited the lowest impedance values, while coated samples showed a significant increase in impedance. For epoxy coating, the real impedance (Z’) was 8×104 Ω with a single layer and increased to 4×105 Ω with two layers. In comparison, flintkote coatings demonstrated much higher impedance values, reaching 1.5×107 Ω, particularly with two layers. The substantial increase in impedance indicates that flintkote provides superior barrier properties compared to epoxy, and that applying multiple layers further enhances corrosion resistance. Therefore, two-layer flintkote coating was found to be the most effective in improving the corrosion resistance of SS400 steel in artificial seawater.